The small school: A case study of school education - Dominik Dvořák; Karel Starý; Petr Urbánek; Martin Chvál (Czech Pedagogical Society, 2010)
A major educational reform of the primary and lower secondary schoolsstarted in the Czech Republic in 2007. Shortly after the launch of the reform, westudied the actual picture of teaching, learning, and instructional leadership in oneCzech comprehensive school, using the design research of a case study. Both qualitativeand quantitative methods were used to describe the educational processes in the school- predominantly questioning, observation, and documentary analysis. Using qualitativedata analysis we have sketched a narrative that highlights the role of structural factors- the small size of the school, the co-existence of primary and lower secondary schoolswithin one organisation, as well as its unique history. The research results describea case of schooling at the very beginning of educational reform, and guide the designof our next case studies of schools.